2006
DOI: 10.1254/jphs.fp0050041
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidative Effects of Astragalus Saponin I Protect Against Development of Early Diabetic Nephropathy

Abstract: Abstract. It has been known that oxidative stress plays an important role in the development of diabetic nephropathy (DN). The antioxidative effects of Astragalus saponin I (AS I) were studied in vitro and in vivo. In the presence of high glucose and H 2 O 2 , the total antioxidative capability, catalase, reduced glutathione, and superoxide dismutase level of rat mesangial cells were significantly decreased, and transforming growth factor β1 (TGF-β1) mRNA level, collagen IV, and laminin level were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…In the present study, both high glucose and H 2 O 2 led to npg increased TGF-β1 protein and mRNA expression in rat MCs, and these were then reduced by treatment with DPI, suggesting that ROS mediated high glucose-induced TGF-β1 production. Our previous reports have demonstrated that TGF-β1 protein and mRNA expression were increased in the renal cortices of diabetic rats [6][7][8] . These findings indicate that TGF-β1 plays an important role during hyperglycemia.…”
Section: Cell Proliferation In the Rat Mesangial Cellsmentioning
confidence: 94%
See 3 more Smart Citations
“…In the present study, both high glucose and H 2 O 2 led to npg increased TGF-β1 protein and mRNA expression in rat MCs, and these were then reduced by treatment with DPI, suggesting that ROS mediated high glucose-induced TGF-β1 production. Our previous reports have demonstrated that TGF-β1 protein and mRNA expression were increased in the renal cortices of diabetic rats [6][7][8] . These findings indicate that TGF-β1 plays an important role during hyperglycemia.…”
Section: Cell Proliferation In the Rat Mesangial Cellsmentioning
confidence: 94%
“…TGF-β1, a very important growth factor in DN pathogenesis, has been reported to be up-regulated in the kidney under diabetic conditions using in vitro [20][21][22][23]25] and in vivo [6][7][8]24] studies. In the present study, both high glucose and H 2 O 2 led to npg increased TGF-β1 protein and mRNA expression in rat MCs, and these were then reduced by treatment with DPI, suggesting that ROS mediated high glucose-induced TGF-β1 production.…”
Section: Cell Proliferation In the Rat Mesangial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…More important, several investigations in the setting of experimental diabetic nephropathy using different drugs, such as mycophenolate mofetil, methotrexate, and erythromycin, have shown that prevention of the development or amelioration of renal injury in diabetes is associated with ant-inflammatory actions (3 -6). More recently, much attention has also been focused on the role of oxidative stress, and it has been suggested that oxidative stress might constitute the key and common events in the pathogenesis of diabetic nephropathy (7,8). Therefore, amelioration of diabetic oxidative stress may prevent or attenuate renal abnormalities associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%